KEBIJAKAN PENINGKATAN PENDAPATAN ASLI DAERAH KOTA TERNATE DARI SEKTOR PAJAK DAERAH DALAM MENUTUPI DEFISIT FISKAL (TAHUN ANGGARAN 2012-2014) - Suleman Samuda (NATAPRAJA, 2016)
The aims of the research is to review the policy of increase locally derived revenue from local tax sector taken by the Local Revenue Office (DISPENDA) municipality of Ternate as one of the instruments to tackle the fiscal deficit in the fiscal year 2012- 2014. The method used in this study is a qualitative approach with descriptive analysis that aims to explore a phenomenon or social fact and then classified based on the clarifications performed by describing a number of variables relevant to the problem. The location was chosen as the object of this study is Local Revenue Office (DISPENDA) municipality of Ternate. The result showed the policy implemented by Local Revenue Office includes cross functional integration as an effort to maximize the availability of the tax authorities through actions combine several jobs into one job and formed coordinator of each local tax which is responsible for the management of the local taxes.Keywords: Fiscal Policy, PAD, and Local Taxes.